A High Comorbidity Score Should Not be a Contraindication for Kidney Transplantation. Issue 2 (February 2016) - Laging, Mirjam; Kal-van Gestel, Judith A.; van de Wetering, Jacqueline; IJzermans, Jan N. M.; Betjes, Michiel G. H.; Weimar, Willem; Roodnat, Joke I.
Abstract : Background: Currently, potential kidney transplant patients more often suffer from comorbidities. The Charlson Comorbidity Index (CCI) was developed in 1987 and is the most used comorbidity score. We questioned to what extent number and severity of comorbidities interfere with graft and patient survival. Besides, we wondered whether the CCI was best to study the influence of comorbidity in kidney transplant patients. Methods: In our center, 1728 transplants were performed between 2000 and 2013. There were 0.8% cases with missing values. Nine pretransplant comorbidity covariates were defined: cardiovascular disease, cerebrovascular accident, peripheral vascular disease, diabetes mellitus, liver disease, lung disease, malignancy, other organ transplantation, and human immunodeficiency virus positivity. The CCI used was unadjusted for recipient age. The Rotterdam Comorbidity in Kidney Transplantation score was developed, and its influence was compared to the CCI. Kaplan-Meier analysis and multivariable Cox proportional hazards analysis, corrected for variables with a known significant influence, were performed. Results: We noted 325 graft failures and 215 deaths. The only comorbidity covariate that significantly influenced graft failure censored for death was peripheral vascular disease. Patient death was significantly influenced by cardiovascular disease, other organ transplantation, and the total comorbidity scores. Model fit was best with the Rotterdam Comorbidity in Kidney Transplantation score compared to separate comorbidity covariates and the CCI. In the population with the highest comorbidity score, 50% survived more than 10 years. Conclusions: Despite the negative influence of comorbidity, patient survival after transplantation is remarkably good. This means that even patients with extensive comorbidity should be considered for transplantation.